2013
DOI: 10.3109/13880209.2013.771375
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of rutin against acute gastric mucosal lesions induced by ischemia-reperfusion

Abstract: Context: Rutin, a flavonoid commonly present in onions, apples and tea, has been suggested to have a variety of pharmacological activities, including immunomodulator, anti-inflammatory and antioxidant activities. Objectives: The present study was to examine the protective effects of rutin on gastric mucosal damage induced by gastric ischemia-reperfusion (I/R) in rats. Materials and methods: Rutin (50, 100, 200 mg/kg) was administered intragastrically for five consecutive days before ischemia. Sixty minutes aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…NO in the body is generated by NOS catalysis, which has cytotoxic effects and is involved in mediating immune reactions [30]. In recent years, studies have shown that many pathological stomach disease processes are associated with abnormal changes of NO levels [30,31]. As the only synthetase of NO, the distribution and function of NOS in the stomach is a hotspot of current research.…”
Section: Resultsmentioning
confidence: 99%
“…NO in the body is generated by NOS catalysis, which has cytotoxic effects and is involved in mediating immune reactions [30]. In recent years, studies have shown that many pathological stomach disease processes are associated with abnormal changes of NO levels [30,31]. As the only synthetase of NO, the distribution and function of NOS in the stomach is a hotspot of current research.…”
Section: Resultsmentioning
confidence: 99%
“…Rutin has a strong antioxidant effect, which can inhibit the damage and aggravation of gastric mucosa caused by oxidative stress [38]. At the same time, rutin can inhibit the excessive production of NO caused by inflammation, thus inhibiting the increase of iNOS activity in gastric mucosa, while increasing the activity of constitutive NOS (cNOS), inhibiting lymphocyte infiltration in gastric mucosa tissue and playing a protective role in gastric mucosa [39]. The preventive effect of AJWTF on gastric injury may also be due to this mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…In the development of peptic ulcer, recruitment of neutrophils and other inflammatory cells to the damaged sites activates secreted enzyme MPO, which promotes oxidative stress [ 91 , 92 ]. Flavonoids, such as quercetin [ 43 ], quercitrin and afzelin [ 45 ], genistein [ 62 ], aromadendrin-4′- O -methyl-ether and kaempferide [ 84 ], kaempferol [ 93 ], and rutin [ 94 , 95 ], have been shown to decrease MPO levels, thereby exhibiting anti-inflammatory activity in peptic ulcer.…”
Section: Anti-ulcer Mechanisms Of Flavonoidsmentioning
confidence: 99%
“…However, inflammation triggers upregulation of inducible nitric oxide synthase (iNOS) in macrophages and neutrophils, which increases NO levels and results in cytotoxic effects and gastric oxidative damage [ 96 , 97 , 98 ]. Pretreatment with rutin at doses of 50, 100, and 200 mg/kg exhibited gastroprotective effects against gastric ulcer induced by ischemia-reperfusion by preventing elevation of iNOS activity and by inhibiting cNOS and MPO activity in the gastric mucosa [ 94 ]. Indomethacin administration decreased the total nitrite/nitrate level in gastric mucosa, which may be related to a decreased production of cNOS in gastric tissue and upregulation of iNOS in neutrophils and macrophages.…”
Section: Anti-ulcer Mechanisms Of Flavonoidsmentioning
confidence: 99%